Supercurrent and Multiple Andreev Reflections in InSb Nanosheet SNS Junctions. Issue 6 (16th January 2019) - Zhi, Jinhua; Kang, Ning; Li, Sen; Fan, Dingxun; Su, Feifan; Pan, Dong; Zhao, Shiping; Zhao, Jianhua; Xu, Hongqi
Abstract : In this study, the realization of mesoscopic Josephson junctions based on free‐standing InSb nanosheet grown by molecular‐beam epitaxy is reported. Below the critical temperature of superconducting aluminium electrodes (≈1.1 K), the high transparency of the contacts gives rise to proximity‐induced superconductivity. A dissipationless supercurrent which can be modulated by a gate voltage acting on the electron density in the nanosheet flows through the superconducting weak links. At finite bias voltage, subharmonic energy‐gap structures (SGS) originating from multiple Andreev reflections (MARs) are observed, indicating a highly transparent InSb nanosheet–superconductor interface. At last, a superconducting hybrid device with niobium electrodes is shown, suitable for further higher temperature and magnetic field transport measurements. Abstract : This study reports the realization of mesoscopic Josephson junctions based on InSb nanosheet. Below the critical temperature of superconducting aluminium electrodes, a dissipationless supercurrent flows through the superconducting weak links. It can be modulated by a gate voltage. At finite bias voltage, subharmonic energy‐gap structures originating from multiple Andreev reflections are observed. At last, a superconducting hybrid device with niobium electrodes is shown for further measurements.